Can the green credit policy stimulate green innovation of heavily polluting enterprises in China? - Xiong, Xiaojuan; Masron, Tajul Ariffin; Gondo, Tutik Wiryanti (Frontiers in Environmental Science, 2023)
The need for more funds has been a significant challenge for China's heavily polluting enterprises (HPEs) to embark on green innovation. This paper takes China's 2012 Green Credit Guidelines (GCGs) as a quasi-natural experiment to examine their effect on the quality and quantity of green innovation in HPEs. We find that the GCGs significantly improve the number of enterprises' green innovation but could not have significantly improved the quality, using the data of Chinese listed companies from 2007 to 2020 and the difference-in-differences (DID) model. As part of the potential solutions, this study proposes (i) the implementation of specific green fiscal policies to complement the existing green credit policies by the government, (ii) a more comprehensive range of green financing products by financial institutions, and (iii) the active development of funding from non-bank sources, such as venture capital or commercial credit.